A Qualitative Research Synthesis Examining the Effectiveness of Interventions Used by Occupational Therapists in Mental Health. (June 2014) - Wimpenny, Katherine; Savin-Baden, Maggi; Cook, Clare
Introduction: To date, a range of qualitative studies have been undertaken in intervention effectiveness, but none has synthesized such studies within the occupational therapy mental health literature. This research article presents a qualitative research synthesis that identifies those interventions used by occupational therapists, internationally, which are viewed as effective from both clients' and carers' perspectives. Method: Qualitative research synthesis was used to analyse, synthesize, and interpret results from qualitative studies. Twenty-two studies, collectively capturing client, carer, and occupational therapists' perspectives, were synthesized by the research team. Findings: The findings identified four themes, which indicated that the occupational therapist needs to exhibit professional artistry, facilitate occupational engagement, pace occupation to support the achievement of client goals and new horizons ; and also recognized the importance of inclusion that promotes client participation and a sense of belonging in a range of socio-cultural contexts. Conclusion: The use of occupational interventions that provide space for healing, self-rediscovery, identity formation, and community participation, were valued more than short, psychological-based interventions focused on case management and the assessment of mental stability, which were seen as superficial in scope. Occupational therapists need to demonstrate an authentic therapeutic relationship that is built upon care, trust, and respect, in order for interventions to have impact.